Ivana Trump's bad Bildung. Issue 12 (1st December 2020) - Hardie, Melissa
ABSTRACT: The celebrity novel seeks to cordone a ground of protected or heightened speech by demarcating that speech as literary and formal, with the privileges that literary form provides. A novel genre such as Bildungsroman serves this purpose especially well since its generic affordances both bolster claims to literary distinctiveness and arguably mechanise or at least facilitate the reorientation of historical events and facts into literary plot and character. I focus on Ivana Trump's 1992 celebrity novel object For Love Alone and the telemovie made of it several years later. Trump's storyline centres on the novelistic 'private' experience of adultery and the reaction to it registered in public action. As such, its calculation of the formation of identity is an important registration of what Corey Robin describes as the 'reactionary mind'. The novel object offers 'bad Bildung ' in generic, psychical and political terms. The mise-en-scene of the telemovie motivates and expresses the formation of 'bad' character and a more social conceptualisation of Bildung as shared enterprise. That sharing is mediated through the article as a variety of social media, televisual collaboration, and the financialisation of the family.